2014
DOI: 10.1007/s10725-014-9966-0
|View full text |Cite
|
Sign up to set email alerts
|

The alleviation of cadmium toxicity in oilseed rape (Brassica napus) by the application of salicylic acid

Abstract: To assess the potential role of salicylic acid (SA) in plants under cadmium (Cd) stress, a study was conducted on three different oilseed rape (Brassica napus) genotypes. Gas exchange parameters, photosynthetic pigments, antioxidant enzymes activities, mineral nutrients concentration, and ultrastructural analysis were carried out for assessment. Interestingly, cadmium treatment reduced gas exchange parameters, photosynthetic pigments, mineral elements [calcium (Ca), magnesium (Mg), and iron] and the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 75 publications
3
38
0
Order By: Relevance
“…Reduction in heavy metal uptake in response to exogenous application of stress hormones can be attributed to the reduced T r and symplastic loading of Cd into the xylem (Lux et al, 2011). However, a relatively higher T r and reduced Cd translocation into the leaves in JA-treated plants were observed and correspond with our previous findings (Ali et al, 2015), where low Cd accumulation and high T r were observed in rapeseed after SA application. Besides transpiration, metal uptake in the plant can also be influenced by other factors, such as accumulation/exudation of organic compounds such as phenolic compounds.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Reduction in heavy metal uptake in response to exogenous application of stress hormones can be attributed to the reduced T r and symplastic loading of Cd into the xylem (Lux et al, 2011). However, a relatively higher T r and reduced Cd translocation into the leaves in JA-treated plants were observed and correspond with our previous findings (Ali et al, 2015), where low Cd accumulation and high T r were observed in rapeseed after SA application. Besides transpiration, metal uptake in the plant can also be influenced by other factors, such as accumulation/exudation of organic compounds such as phenolic compounds.…”
Section: Discussionsupporting
confidence: 89%
“…These results agree with the findings of Piotrowska et al (2009) which state that JA application significantly inhibits Pb accumulation in W. arrhiza. In addition, other stress hormones, such as salicylic acid (SA), abscisic acid (ABA), and brassinolide (2,4-epibrassinolide), can reduce the uptake of toxic metals (Cd or nickel (Ni)) in hydroponic and soil-grown plants (Kanwar et al, 2012;Ali et al, 2015). Reduction in heavy metal uptake in response to exogenous application of stress hormones can be attributed to the reduced T r and symplastic loading of Cd into the xylem (Lux et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are researches comparing several types of PGR that are close to the mode of action (StoynovaBakalova, Petrov, 2010;Choudhary et al, 2011), the effectiveness of several concentrations of the PGR (Gangwar et al, 2011), different exposure times (treatment times) with the PGR (Canakci, Dursun, 2011), the effectiveness of PGR in plants under several types of environmental stress (Fariduddin et al, 2013) or the effectiveness of PGR on several species/genotypes (Ali et al, 2015).…”
Section: Introductionmentioning
confidence: 99%